2018
DOI: 10.3390/educsci8020052
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Health-Related Quality of Life in Adults from Braşov, Romania

Abstract: (1) Background: This study aims to investigate the association between different levels of physical activity (PAL) and health-related quality of life (HRQoL) in a random sample of the adult population; (2) Methods: The study material comprised 1100 adults of the city of Brasov, Romania (700 men, 400 women), aged 30-45 years old. We used the short version of the International Physical Activity Questionnaire Short Form (IPAQ-SF) and Short-Form Health Survey (SF-36) to assess PAL and HRQoL, respectively; (3) Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…Physical activity and its impact on population health is one of the problems actively studied in the field of physical education. Studies of the lev-el of physical activity and its impact on the quality of life of adult population showed that the highest levels of physical activity positively affect the quality of life (Bădicu, & Balint, 2016;Bădicu, 2018). Physical education of schoolchildren aims at optimizing the child's physical development (Balsevich, 2000;Novak, Podnar, Emeljanovas, Marttinen, 2015), improving the process of motor skills development and teaching physical ex- ISSN 1993-7989 (print).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and its impact on population health is one of the problems actively studied in the field of physical education. Studies of the lev-el of physical activity and its impact on the quality of life of adult population showed that the highest levels of physical activity positively affect the quality of life (Bădicu, & Balint, 2016;Bădicu, 2018). Physical education of schoolchildren aims at optimizing the child's physical development (Balsevich, 2000;Novak, Podnar, Emeljanovas, Marttinen, 2015), improving the process of motor skills development and teaching physical ex- ISSN 1993-7989 (print).…”
Section: Introductionmentioning
confidence: 99%
“…Motor activity and its impact on the health of the population is one of the problems actively studied in the field of physical education [1,2]. Physical education of schoolchildren is aimed at optimizing the physical development of the child [3,4], improving the process of development of motor abilities [5,6], strengthening and health [7].…”
mentioning
confidence: 99%
“…Behavioural factors are also associated with reduced HRQoL in elderly people. 9,10 Several researchers have recently investigated the social and psychological effects on elderly Chinese people of living alone or with a spouse, but without the support of extended family. 11 However, most of these studies have focused on rural communities or the psychological effects of living unsupported.…”
Section: Introductionmentioning
confidence: 99%